2010
DOI: 10.1093/brain/awq221
|View full text |Cite
|
Sign up to set email alerts
|

Motor and cognitive outcome in patients with Parkinson's disease 8 years after subthalamic implants

Abstract: Deep brain stimulation of the subthalamic nucleus represents the most important innovation for treatment of advanced Parkinson's disease. Prospective studies have shown that although the beneficial effects of this procedure are maintained at 5 years, axial motor features and cognitive decline may occur in the long term after the implants. In order to address some unsolved questions raised by previous studies, we evaluated a series of 20 consecutive patients who received continuous stimulation for 8 years. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

34
365
5
14

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 362 publications
(418 citation statements)
references
References 67 publications
34
365
5
14
Order By: Relevance
“…Our findings agree with what observed in other studies [6], [7] and [8], and could be chiefly explained by the progression of the disease over time [16]. While the cardinal PD symptoms keep on improving with stimulation, there is a progressive emerging of poorly levodopa-responsive symptoms, mainly axial symptoms, speech problems and postural instability.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our findings agree with what observed in other studies [6], [7] and [8], and could be chiefly explained by the progression of the disease over time [16]. While the cardinal PD symptoms keep on improving with stimulation, there is a progressive emerging of poorly levodopa-responsive symptoms, mainly axial symptoms, speech problems and postural instability.…”
Section: Discussionsupporting
confidence: 92%
“…STN-DBS efficacy on PD motor symptoms is well documented in the short-and medium-term, up to 5-6 years [4] and [5], while a few papers with a small number of examined patients addressed the long-term efficacy of this procedure [6], [7] and [8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, longterm follow-up studies on STN-DBS treated patients [5,7] demonstrated that stimulation efficacy could be limited by the progressive development of neuropsychological alterations, even though few data have been reported on the long-term STN-DBS outcomes in relation to the baseline cognitive performances. The majority of follow-up studies focused only on patients reaching the long-term evaluation, without considering subjects who developed dementia or died after a variable period of time after DBS.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4] Because levodopa-responsive parkinsonian symptoms are improved by high-frequency stimulation of the subthalamic nucleus, 5,6 neurostimulation has become an established treatment for advanced Parkinson's disease with medically intractable fluctuations and dyskinesia [7][8][9][10] and has shown long-term efficacy. [11][12][13] It is typically used after the disease has been present for 11 to 13 years, 7-10 when quality of life, social adjustment (psychosocial competence), 14 and professional activity are already severely impaired. Neurostimulation improves quality of life, [7][8][9][10] in addition to motor symptoms.…”
mentioning
confidence: 99%